Today's state‐owned enterprises of China: are they dying dinosaurs or dynamic dynamos? - Ralston, David A.; Terpstra-Tong, Jane; Terpstra, Robert H.; Wang, Xueli; Egri, Carolyn P. (Strategic Management Journal, 2006)
Abstract This paper raises the question and provides empirical evidence regarding the status of the evolution of the state‐owned enterprises (SOEs) in China today. In this study, we compare the SOEs to domestic private‐owned enterprises (POEs) and foreign‐controlled businesses (FCBs) in the context of their organizational cultures. While a new ownership form, many of the POEs evolved from former collectives that reflect the traditional values of Chinese business. Conversely, the FCBs are much more indicative of the large global MNCs. Therefore, we look at the SOEs in the context of these two reference points. We conclude that the SOEs of today have substantially transformed to approximate a configuration desired by the Chinese government when it began the SOE transformation a couple of decades ago to make them globally competitive. The SOEs of today appear to be appropriately described as China's economic dynamic dynamo for the future. Copyright © 2006 John Wiley & Sons, Ltd.